Industry response to strengthened regulations: amount and themes of flavoured electronic cigarette promotion by product vendors and manufacturers on Instagram. (3rd November 2022) - Kostygina, Ganna; Tran, Hy; Schillo, Barbara; Silver, Nathan A; Emery, Sherry L
Abstract : Background: Social media discussion tends to follow news about proposed or enacted government policies. Thus, digital discourse surveillance may be an effective and unobtrusive way of understanding industry and public response to policies and regulations, including in the domain of tobacco control. Recently, the US Food and Drug Administration restricted sales of flavoured cartridge and disposable vape products. Historically, the tobacco industry used modification of product characteristics, labelling or packaging to work around flavour restrictions. We aimed to characterise strategies used by nicotine product manufacturers and vendors to promote flavoured products on Instagram and to identify policy workaround tactics. Methods: Keyword rules were used to collect flavoured electronic cigarette-related Instagram posts from CrowdTangle, from 1 January 2019 to 31 December 2021. Posts were coded for commercial content and promotional strategies using a combination of machine learning methods, keyword algorithms and human coding. Additional exploratory analyses were conducted to identify major discussion themes. Non-English posts were excluded from the analyses. Results: Keyword filters captured 113 393 relevant posts from 391 unique accounts, with 46 076 posts referencing flavour promotion (40.6%) and 2124 (2%) posts mentioning alternatives to restricted flavoured products or strategies to evade flavour sales restrictions. Promotional messages featured non-characterising flavour references, 'off-brand' product substitutes, promotion of new flavoured product technologies, innovation, do-it-yourself appeals, global promotion, international delivery and encouraged flavoured product stockpiling. In addition, promotion of refillable devices, e-juice, tank systems and 'box mod' vaporizers was present. Conclusion: Social media surveillance can enhance our understanding of public health needs and policy compliance, as well as inform strategies to prevent policy evasion. Examining evolving industry tactics to promote flavoured products in response to regulatory changes can help authorities and practitioners assess policy effectiveness and inform future design and implementation approaches.